Preparation of Silver Immobilised TiO2-Hectorite for Phenol Removal and Eschericia coli Desinfection - Is Fatimah (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Preparation of silver immobilized TiO2-Hectorite and its application in phenol photooxidation and Eschericia coli bacteria desinfection has been conducted. Material was obtained by two steps of synthesis: preparation of TiO2-Hectorite and silver immobilization into TiO2-Hectorite. Physico-chemical characterization to the prepared material compared to raw hectorite was conducted by X-ray Diffraction, gas sorption analyzer, scanning electron microscope and DRUV-Visible spectrophotometry and for photoactivity study, phenol photooxidation and Eschericia coli desinfection were investigated. The results indicated that the modification to hectorite material improve the physico-chemical character related to its role as photo-catalyst. Kinetic study of phenol photooxidation revealed the role of TiO2 pillarization and silver immobilization in enhancing rate of reaction as well as increased photoactivity of the materials in E. coli desinfection. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)